CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Simplify the following:
$$(2x + 5y)^2 + (2x - 5y)^2$$


Solution

$$(2x + 5y)^2 + (2x - 5y)^2$$      $$[Using, \ (a \pm b)^2 = a^2 \pm 2ab + b^2]$$
$$ = (2x)^2 + 2 \times 2x \times 5y + (5y)^2 + (2x)^2 - 2 \times 2x \times 5y + (5y)^2$$
$$ = 4x^2 + 20xy + 25y^2 + 4x^2 - 20xy + 25y^2$$
$$ = 8x^2 + 50y^2$$

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image